2015
DOI: 10.1007/s12031-014-0486-1
|View full text |Cite
|
Sign up to set email alerts
|

Nampt/PBEF/Visfatin Exerts Neuroprotective Effects Against Ischemia/Reperfusion Injury via Modulation of Bax/Bcl-2 Ratio and Prevention of Caspase-3 Activation

Abstract: Nicotinamide phosphoribosyl transferase/pre-B cell colony-enhancing factor/visfatin (Nampt/PBEF/visfatin) is an adipocytokine. By synthesizing nicotinamide adenine dinucleotide (NAD(+)), Nampt/PBEF/visfatin functions to maintain an energy supply that has critical roles in cell survival. Cerebral ischemia leads to energy depletion and eventually neuronal death by apoptosis in specific brain regions specially the hippocampus. However, the role of Nampt/PBEF/visfatin in brain and cerebral ischemia remains to be i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 28 publications
6
44
0
Order By: Relevance
“…In the present study, we also showed that AAV-mediated PBEF overexpression significantly reduced caspase-3 activation during OGD stimulation in primary neuronal cultures. This finding is consistent with results showing that inhibition of PBEF by its inhibitor FK866 increases the expression of cleaved caspase-3 in OGD model of cultured neurons and recombinant PBEF administration through intracerebroventricular injection decreases caspase-3 activity in the rat hippocampal CA3 region after transient global cerebral ischemia836. Thus our study has established that PBEF can protect against apoptotic neuronal death through both caspase-independent and caspase-dependent pathways.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, we also showed that AAV-mediated PBEF overexpression significantly reduced caspase-3 activation during OGD stimulation in primary neuronal cultures. This finding is consistent with results showing that inhibition of PBEF by its inhibitor FK866 increases the expression of cleaved caspase-3 in OGD model of cultured neurons and recombinant PBEF administration through intracerebroventricular injection decreases caspase-3 activity in the rat hippocampal CA3 region after transient global cerebral ischemia836. Thus our study has established that PBEF can protect against apoptotic neuronal death through both caspase-independent and caspase-dependent pathways.…”
Section: Discussionsupporting
confidence: 92%
“…For example, in the myocardial injury model, PBEF can delay or inhibit mitochondrial permeability transition pore (mPTP) opening both in situ murine heart and the isolated murine cardiomyocytes52. Meanwhile, PBEF was found to inhibit apoptosis and prevent metabolic dysfunction via regulating the expression of mitochondrial-dependent anti-apoptotic protein Bcl-2, as well as pro-apoptotic proteins, such as Bax and cytochrome C36. These regulations depend on the activation of pro-survival kinases, PI3K/AKT and MEK1/2, mediated-signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Nampt levels are reduced with aging and stress (Hsu et al , 2009), resulting in decreased NAD + and decreased SIRT1 activity (Imai, 2011). Accordingly, overexpression of Nampt in the heart (Hsu et al , 2009) and brain (Erfani et al , 2015) has been shown to reduce infarct size and apoptosis in response to ischemia and reperfusion. In a negative feedback loop, Nampt is also regulated by SIRT1 mediated deacetylation and inactivation of its transcription factors (Ramsey et al , 2009).…”
Section: Pharmacologic Therapiesmentioning
confidence: 99%
“…We are faced with technical limitations in separating the CA3 area from other parts of the hippocampus for RT-PCR and Western blot analysis; we used immunohistochemical staining to better detect protein expression. Immunohistochemical staining was performed on 7-lm tissue sections (three sections per animal) [28]. Briefly, tissue sections were incubated for 30 min at 60°C, rehydrated through a descending alcohol series and treated with 10 % hydrogen peroxide in methanol for 10 min to reduce endogenous peroxidase activity.…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%